1989
DOI: 10.1192/bjp.154.4.544
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Extreme Temperament in Infancy for Clinical Status in Preschool Years

Abstract: Few, if any, of children's behavioural or cognitive characteristics assessed in the first years of life demonstrate stability until later childhood; early characteristics have so far failed to show an association with future psychopathology. This longitudinal study, from 4-8 months to 4.7 years old, focused on stability and change of extreme temperamental traits in groups of infants subselected from a large birth cohort. Persistent extreme temperament at four and eight months old did not increase stability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Much research has used global categorisations of temperament such as 'easy' and 'difficult' (e.g. Lee & Bates, 1985;Maziade, Cote, Bernier, Boutin, & Thivierge, 1989). However, a focus of recent research has been the identification of relationships between specific temperament traits and behavioural adjustment.…”
Section: Temperament and Behaviour Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Much research has used global categorisations of temperament such as 'easy' and 'difficult' (e.g. Lee & Bates, 1985;Maziade, Cote, Bernier, Boutin, & Thivierge, 1989). However, a focus of recent research has been the identification of relationships between specific temperament traits and behavioural adjustment.…”
Section: Temperament and Behaviour Problemsmentioning
confidence: 99%
“…A few studies have included measures of both parenting style, conceptualised in a variety of ways (e.g. Maziade, et al, 1989;, and temperament, and have indicated that each makes an independent contribution to children's behaviour. Prior et al, for example, reported that in 6-7 year old girls, temperament dimensions (inflexibility and persistence) as well as punitive parenting had direct paths to behaviour problems, concurrently and at a 12 month follow-up.…”
Section: Parenting and Behaviour Problemsmentioning
confidence: 99%
“…Studies examining the direct effects of domains are found more often in families difficult temperament on later externalizing from lower socioeconomic backgrounds (Rich-behavior problems in the preschool and man, Stevenson, & Graham, 1982;Rutter, school-age periods have shown modest to 1978). However, because multiple risk factors moderate relations (Maziade, Cote, Bernier, tend to cluster in the same low socioeconomic Boutin, & Thivierge, 1989;Sanson et al, status (SES) environments, it has been diffi-1991). cult to disentangle the exact pathways leading Infant attachment security also has been from risk to the development of disruptive be-found to be related to later externalizing probhavior problems.…”
mentioning
confidence: 99%
“…This sampling methodology ensured that relatively rare examples of defined hemi‐bun morphology were represented. Similar methods of extreme case sampling have been successfully used in a number of fields, including paleoanthropological (Maddux & Franciscus, ), behavioral (Maziade, Cote, Bernier, Boutin, & Thivierge, ), and genetic (Li, Lewinger, Gauderman, Murcray, & Conti, ; Nebert, ) studies. The primary questions posed by the present study, involving spatial dynamics and covariation patterns associated with distinct hemi‐bun morphology, can be most clearly addressed using this nonrandom sampling methodology.…”
Section: Methodsmentioning
confidence: 99%